Perception of Students on the Use of Mobile Phones in EFL Learning: A Phenomenological Study - Tembe, Harka Raj (Rupantaran: A Multidisciplinary Journal, 2021)
This research study focuses on the students’ perception on the use of mobile phones in EFL learning in the context of Nepal. It aims to investigate how the students are taking smart phones as a means for EFL learning in their educational experience. The study was carried out among the students of the bachelor level at Dhankuta Multiple Campus. It was largely informed by a phenomenological approach in order to examine the students’ experiences of using mobile phones in EFL learning. The semi- structured interview was held to collect the required data. Results indicate that all participants have positive attitudes on the use of mobile phones in learning English. However, they feel a few difficulties in understanding the text through the mobile phones. They expect supportive guidance and reliable network quality for effective EFL learning. Mobile phones can serve as a useful language learning tool if it is utilized properly for specific purposes. All curriculum developers, syllabus designer and policy makers should consider the space of mobile assisted English language learning in the present curriculum.